The Influence of Attachment Styles On Marital Satisfaction On A Wife Who Has Been Cheated - Maria Yuni Megarini Cahyono; Yuspendi Yuspendi; Nuria Ristnawati Nanrimansyah (Faculty of Social Science, Universitas Negeri Padang, 2023)
Infidelity is the main cause of divorce in West Java, which harms individuals, especially wives who are victims of infidelity. In response to infidelity, wives are more likely to react with intense emotions that tend to last a long time, and it is easier to recall the incident, thus requiring more attention. The subjects of this study were 55 individuals whose wives were aged 18-40 years and had experiences of being cheated on and domiciled in the city of Bandung. This study aimed to describe the effect of Attachment Styles on the Marital Satisfaction of wives who had been cheated on in Bandung. The research method used is quantitative. The measuring instrument used to obtain individual Attachment Styles is The Experience in Close Relationships-Revised (ECR-R) Questionnaire, which consists of 36 items referring to the theory of Bartholomew and Horitz and consists of 36 items. The measuring instrument used to obtain the degree of individual Marital Satisfaction is ENRICH MARITAL SATISFACTION, compiled by Olson & Fowers (1993), consisting of 15 items with 4 answer choices. Subjects in this study will be given both questionnaires. After that, the results of the two questionnaires will be analyzed using a simple regression method. The results showed that attachment style strongly influences and can predict 31% of marital satisfaction in wives cheated on.